PMO-068 Timing of parenteral nutrition administration set changes: impact on incidence of catheter associated infections. (28th May 2012) - Driver, R; Mistry, P; Swain, D; Colinese, E; Saich, R
Abstract : Introduction: Preparations of total parental nutrition (TPN) are stable for 48 h. For patients with requirements <2.5l/24 h individual bags of TPN are delivered for more than 24 h, resulting in cost savings and less frequent manipulations of the administration set. The epic2 guidelines recommend that administration sets exposed to lipids must be changed every 24 h to reduce possible line sepsis, effectively prohibiting the delivery of TPN bags over a period >24 h. The objective of this study is to determine whether the incidence of central venous catheter (CVC) associated infection is increased by running TPN over a period of >24 h compared to <24 h. Methods: We analysed the CVC infection rate for 550 patients receiving TPN over a 3-year period, a total of 8339 line days. We assigned each CVC line into two groups; those through which at least one bag of TPN had been run for more than 24 h (1063 CVC lines) and those in which every bag was changed within 24 h (166 CVC lines). CVC-associated infection was confirmed when the same organism was grown on central and peripheral blood cultures, or blood culture and CVC tip culture. Information on CVC line position, duration and complication rate was also collected. Results: The CVC infection rate was 3.26/1000 line days in the >24 h group (95% CI 3.0 to 3.5) and 3.14/1000 line days in the <24 h group (1.6 to 4.7). There was no significant difference in the infection rate between the two groups (χ 2, p=0.84). Conclusion: Administering TPN via a single giving set over a period >24 h does not increase the incidence of central venous catheter associated infections. Competing interests: None declared. Reference: 1. Pratt RJ, Pellowe CM, Wilson JA, et al. Epic2: national evidence-based guidelines for preventing healthcare-associated infections in NHS hospitals in England. J Hosp Infect . 2007;65 (Suppl 1):S1–64.